2021
DOI: 10.1021/acschemneuro.1c00559
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Metabolite Alterations Associated with Neuronal Signals of Caenorhabditis elegans during Cronobacter sakazakii Infections

Abstract: Metabolomic reprogramming plays a crucial role in the activation of several regulatory mechanisms including neuronal responses of the host. In the present study, alterations at physiological and biochemical levels were initially assessed to monitor the impact of the candidate pathogen Cronobacter sakazakii on the nematode host Caenorhabditis elegans. The abnormal behavioral responses were observed in infected worms in terms of hyperosmolarity and high viscous chemicals. The microscopic observations indicated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…24 Later, Muthubharathi et al reported that the metabolites of C. elegans respond negatively to C. sakazakii infection. 25 Further studies also proved that C. sakazakii infection altered the genes of C. elegans involved in pathogen recognition and kinase activity. 26 Despite this limited number of studies, no reports are available regarding the neuro-immune protein change in C. elegans during C. sakazakii infection to date.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…24 Later, Muthubharathi et al reported that the metabolites of C. elegans respond negatively to C. sakazakii infection. 25 Further studies also proved that C. sakazakii infection altered the genes of C. elegans involved in pathogen recognition and kinase activity. 26 Despite this limited number of studies, no reports are available regarding the neuro-immune protein change in C. elegans during C. sakazakii infection to date.…”
Section: Discussionmentioning
confidence: 95%
“…In studies of C. sakazakii interactions, C. elegans has been used as a host. [23][24][25][26] Albeit the transcriptional and metabolomic level studies have been reported by our research group, we aimed to approach more specifically to the functional molecular players involved in crucial neuro-immune signaling pathways. The protein players integrated into the immune system via neuronal signals rapidly contribute to the defense mechanism during the HPI.…”
Section: Introductionmentioning
confidence: 99%
“…Using the Cortecs C18 column, a reversed-phase LC-MS (RP-LC-MS) was performed, showing that the improved combined extraction scheme for lipid and metal species allowed for the simultaneous monitoring and analysis of the lipidomes of the same nematode population, especially iron redox state homeostasis [ 242 ]. Through the LC-MS/MS method, Muthubharathi et al found that a sakazakii infection made the nematode neurotransmitters and fatty acids abnormal, which was associated with the accumulation of LD [ 243 ]. In addition, LC-MS and multiple reaction monitoring (MRM) were also combined to fully characterize the composition and abundance of sphingolipids (SLs) under different developmental stages and growth conditions in nematodes.…”
Section: Experimental Tools For the Studies Of Fat Metabolism In ...mentioning
confidence: 99%
“…The protocol was followed as mentioned in ref. 32. The synchronized L4 stage worms were washed with a M9 buffer.…”
Section: Metabolite Extraction and Sample Preparation For Lc-ms Analysismentioning
confidence: 99%
“…For analyzing the whole metabolome, the metabolites were categorized into endo-metabolome, the metabolites present in the host (also called metabolic fingerprinting), and exo-metabolome, the metabolites secreted out by the host (also called metabolic footprinting). 32 By studying both, the complete profile of metabolites which are synthesized, utilized and secreted out during the interaction of bacteria in C. elegans can be understood. The results indicated that significantly distinct profiles in both endo- and exo-metabolome of C. elegans during S. aureus and S. Typhi interactions could be useful to identify the therapeutic targets in developing bioactives/drugs for metabolic pathway(s) or player(s).…”
Section: Introductionmentioning
confidence: 99%